Killer lipstick and other spy gadgets - Rauf, Don (New York Franklin Watts, 2008)
Know your enemy, and that's the best military strategy. The more a country knows about its enemies, the safer it is, and that's where spies come in and gather knowledge. Some spies are secret agents who work overseas, others stay home supporting agents in the field
Hurg
5 8
Keywords: Intelligence service -- Juvenile literature; Spies -- Juvenile literature